Testing the Construction Site Supervisory Attributes in Applying Green Practices in Construction Operations - Manoharan, Kesavan; Dissanayake, Pujitha; Pathirana, Chintha; Deegahawature, Dharsana; Silva, Renuka (International Journal of Sustainable Construction Engineering and Technology, 2023)
Sources highlight that poor application of green practices, ineffective supervising strategies and inadequate apprenticeship facilities significantly impact the overall efficiency of construction project flows. Accordingly, this research attempts to test the construction supervisory traits in executing green concepts/practices in construction site operations. As part of a newly designed supervisory apprenticeship that was systematically designed utilising consecutive approaches, 59 construction supervisors were evaluated using four key sections of competency characteristics and the relevant learning domains. An assessment tool encompassing various levels of descriptions and criteria was developed using a comprehensive literary analysis and consultations with subject matter experts. The results point to a generalised modern guideline that describes the types of supervision traits related to the application of green concepts/practices that can be theoretically and practically taken into account during the construction process. Using appropriate statistical tests and professional evaluations, the validation and generalisation of the study’s applications were ensured with the reliable-ness of the findings. New standards and recommendations for construction supervision procedures are produced by the research, which might elevate this profession and make it the key determinant of the sustainability of site operations. This paper elaborates on the study’s broad implications and potential future applications in order to close the knowledge gap in the area of developing the application procedures and protocols related to skill enhancement/upgrading. The implementation of the research outcomes will significantly impact future practices in other developing nations and developing industries, even though the supervisory samples were used from the Sri Lankan construction setting.